2011
DOI: 10.1002/jmv.22216
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Amino acid mutation in hepatitis C virus core region among Japanese volunteer blood donors

Abstract: It is not known whether there is a trend of increasing or decreasing incidence of new hepatitis C virus (HCV) infections in Japan. From the treatment point of view, it is important to verify HCV genotypes and the prevalence of treatment-resistant clones of HCV. At the Japanese Red Cross blood centers, all blood samples obtained from blood donation have been screened using serological methods and the minipool nucleic acid amplification testing. One hundred and fourteen donors have been identified over the past … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The most interesting finding of this study is that the amino acid at position 91 is different in HCV‐1b (Lue 91 Met) than HCV‐1a and HCV genotype 4 where Cys 91 is well conserved (Alhamlan et al, unpublished data). In addition, this study is in agreement with a recent study that reported Gln 70 and/or Met 91 are associated with poor response in HCV‐1b subgenotype but not in those with other genotypes [Furui et al, ]. Further investigations are needed to determine the significance of specific mutations in each genotype and how they affect the response to the treatment.…”
Section: Discussionsupporting
confidence: 91%
“…The most interesting finding of this study is that the amino acid at position 91 is different in HCV‐1b (Lue 91 Met) than HCV‐1a and HCV genotype 4 where Cys 91 is well conserved (Alhamlan et al, unpublished data). In addition, this study is in agreement with a recent study that reported Gln 70 and/or Met 91 are associated with poor response in HCV‐1b subgenotype but not in those with other genotypes [Furui et al, ]. Further investigations are needed to determine the significance of specific mutations in each genotype and how they affect the response to the treatment.…”
Section: Discussionsupporting
confidence: 91%
“…As: Asian countries like Ch: China and J: Japan (including prevalence data of Furui et al [39], for which sequences are not available); RW: Rest of the world. Numbers in bold refer to mutations found at higher frequency compared to other genotypes or locations.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with IFN/RBV has been proposed to induce these amino acid mutations [23]. Another possible explanation is that these mutations might be selected during the natural course of infection, in response to the selective pressure of endogenous IFN [39]. The relatively high frequency of these mutations in patients not treated with IFN/RBV might be associated to the transmission of HCV isolates from treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Furui et al (2011) identified aa 70 and aa 91 substitutions among Japanese volunteer blood donors (Furui et al 2011).…”
Section: Discussionmentioning
confidence: 97%